EFEKTIFITAS BLENDED LEARNING MELALUI LMS MOODLE UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA DI POLITEKNIK [THE EFFECTIVENESS OF BLENDED LEARNING USING THE MOODLE LMS TO IMPROVE POLYTECHNIC STUDENTS’ SELF-REGULATED LEARNING IN MATHEMATICS COURSES] - Pratiwi, Indah Riezky (Universitas Pelita Harapan, 2022)
The lack of self-regulated learning of a learner in a series of learning activities often hurts the achievement of their learning outcomes. It is necessary to provide a learning environment that supports an increase in one's self-regulated learning, which is through the application of blended learning. This study aims to look the effectiveness of the application of blended learning using the Moodle LMS in improving Polytechnic students’ self-regulated learning. This study applies a quantitative approach through the pre-experiment method and uses a One-Group Pretest-Posttest research design. This study compares the results of pretest and posttest on experimental class students after applying blended learning using the Moodle LMS. The research instrument analyzed was in the form of a non-test instrument which was arranged in a questionnaire. Statistical tests on research data were processed using SPSS 26 software. Wilcoxon nonparametric test results on questionnaire data gave results in the form of a significance value of 0.00 < 0.05 and the average N-gain value showed a value of 0.64. Through the results of statistical tests that have been carried out, it can be concluded that the application of learning with the blended learning model using the Moodle LMS has implications for increasing self-regulated learning for Polytechnic students with moderate effectiveness criteria.BAHASA INDONESIA ABSTRACT: Kurangnya kemandirian belajar atau self-regulated learning seorang pembelajar dalam serangkaian aktivitas pembelajaran seringkali memberikan dampak yang buruk pada pencapaian hasil belajar mereka. Penyediaan lingkungan belajar yang mendukung peningkatan self-regulated learning seseorang perlu dilakukan, salah satunya melalui penerapan blended learning. Penelitian ini bertujuan untuk melihat tingkat keefektifan penerapan Blended Learning melalui LMS Moodle dalam meningkatkan self-regulated learning mahasiswa di Politeknik. Penelitian ini menerapkan pendekatan kuantitatif melalui metode Pre Eksperiment serta menggunakan desain penelitian One-Group Pretest-Posttest. Penelitian ini membandingkan hasil pretest dan posttest pada mahasiswa kelas eksperimen setelah diterapkan blended learning melalui LMS Moodle. Instrumen penelitian yang dianalisis berupa instrumen bentuk non tes yang disusun dalam sebuah kuisioner. Uji statistik terhadap data hasil penelitian diolah menggunakan software SPSS 26. Hasil uji nonparametric Wilcoxon terhadap data angket memberikan hasil berupa nilai signifikansi 0.00 < 0.05 dan rata-rata nilai N-gain menunjukkan nilai 0.64. Melalui hasil uji statistik yang telah dilakukan dapat disimpulkan bahwa penerapan pembelajaran dengan model blended learning melalui LMS Moodle berimplikasi dalam peningkatan self-regulated learning mahasiswa Politeknik dengan kriteria efektifitas sedang.